Suppose that y = f(x) = x^2-4x+4
Then on any interval where the inverse function y = f^–1(x) exists, the derivative of y = f^–1(x) with respect to x is:
a) 1/(2x-4)
b) 1/(2y-4), where x and y satisfy the equation y=x^2-4x+4
c)(1/2)x^(-1/2)
d)(1/2)x^(1/2)
e) Both 1/(2y-4), where x and y satisfy the equation y=x^2-4x+4 and (1/2)x^(-1/2)
5 answers
Hint: dx/dy = 1/(dy/dx)
That would be 1/(dy/dx) of x^2-4x+4
which would be 1/2x-4 correct?
which would be 1/2x-4 correct?
Wait f^-1(x) is 2sqrt(x) so then the derivative of that is 1/sqrt(x)
c)(1/2)x^(-1/2) is the correct answer
f(x) = x^2-4x+4
y = (x-2)^2
Inverse function
x = (y-2)^2
Differentiate the inverse function, you would get
y' = 1/(2sqrt(x))
y = (x-2)^2
Inverse function
x = (y-2)^2
Differentiate the inverse function, you would get
y' = 1/(2sqrt(x))